An Error Analysis On Writing Descriptive Text Made ByThe Eighth Grade Students Of Smp N 3 KartasuraIn 2015/2016 Academic Year - Sarwati, Tati, Prof. Dr. Endang Fauziati, M.Hum, Dr. Anam Sutopo, S.Pd. M.Hum (2016)
The purpose of this study is to describe the types of learners' error on writing descriptive text by eighth grade students of SMP N 3 Kartasura in 2015/2016 academic year. There are five objectives of the study consists of 1) classifying the type of morphological error, 2) identifying the type of syntactical error, 3) describing the type of discourse error, 4) describing the frequency of types of error, and 5) explaining the sources of error. The type of this study is descriptive qualitative research. The data of this study is erroneous sentence in descriptive text and the data source of this study is document of descriptive text made by eighth grade students. The researcher uses elicitation technique as a technique of collecting the data. There are four steps to collect the data; the researcher comes to the class appropriate with the English schedule of eighth grade students, the researcher asks to write a descriptive text and the researcher waits the students until finish their works, the researcher collects the data of students' writing, then reads and marks the type of errors that occurs in students' writing. The researcher identifies the erroneous sentence, and then classifies the types of errors based on linguistic category and surface strategy taxonomy. The researcher uses James's theory to classify of error, the researcher uses Slamet's theory to count the frequency of type of error, and the researcher uses the theory from Brown, Corder, and Richard to find the sources of error. The result of this research shows that 170 data divided into three types of error namely morphological error, syntactical error, and discourse error. First, there are 72 data or 42, 35% belong to morphological error, second, there are 93 data or 54, 70% belong to syntactical error, and third, there are 5 data or 2, 94% belong to discourse error, fourth, the frequency of type of error is wrong spelling in morphological error with total number of error 52 or 30, 58%, finally, there are two sources of error namely intralingual and interlingual transfer. In the eighth grade students of SMP N 3 Kartasura, they have to more learn about how to make the correct sentence and also distinguish between the spelling of word in their mother tongue (Indonesian language) with the spelling of word in their second language (English language), because the dominant of type of error made by the student is wrong spelling in morphological error.